Challenges of Religious and Cultural Diversity in the Child Protection System with Children Migrating “Alone” in Catalonia and Melilla - Montserrat Freixa Niella; Francisca Ruiz Garzón; Angelina Sánchez-Martí; Ruth Vilà Baños (Religions)
Cultural and religious diversity in Spain, driven by recent decades of migratory flows, has not been exempt from generating social tensions and, unfortunately, an increasing stigmatization of migrant children. This article examines how power dynamics and exclusion impact the identity construction of these young people, particularly within the child protection system. Through interviews and focus groups with young people and professionals in Barcelona and Melilla, this study highlights the resistance strategies these young individuals employ to counteract stigmatizing narratives. The findings indicate that, despite inclusion policies, imposed labels reinforce their vulnerability and limit their social and community participation. Although interfaith dialogue is proposed as a tool to mitigate these tensions, professionals working with these children emphasize the lack of institutional support and insufficient training in socio-cultural diversity, which hinders their efforts. The study underscores the importance of developing interfaith competencies that foster mutual respect and recognition, concluding with a critique of the current protection system. It advocates for a comprehensive approach to addressing these young people’s emotional, social, and spiritual needs beyond solely legal and educational aspects.